Enhancement of the Thermal Stability of Engine Block Alloy Al-10Si-1Cu-0.5Mg-0.5Ni-0.5Fe with Trace Additions of Ti and Zr - Mohammad Salim KAISER (Engineering Transactions)
An investigation was carried out on the Al-10Si-1Cu-0.5Mg-0.5Ni-0.5Fe alloy engine block, emphasizing its physical and mechanical characteristics, as well as the presence of trace titanium (Ti) and zirconium (Zr). Three different alloys underwent processes such as homogenization, T6 solution treatment, quenching, and aging to observe both natural and artificial aging responses. The development of Al2Cu and Mg2Si phases within the aluminum matrix during the aging process led to the attainment of peak-aged strength. However, this strength diminished in the over-aged condition due to precipitation coarsening and recrystallization phenomena. The addition of Ti effectively refined the α-Al grain structure and led to the formation of thermally stable nano-sized Al3Ti dispersoids, which did not significantly enhance  strength but prevented a drastic decline in the strength of the thermally damaged alloy. The simultaneous addition of Ti and Zr to the alloy further facilitated the precipitation of Al3(Ti, Zr) dispersoids, enhancing this capability. Trace addition  reduced the alloys' toughness as well as thermal conductivity to a small extent due to grain refinement  and precipitation formation, but these properties improved during aging due to recovery and recrystallization. Microstructural analysis of the alloys indicated that trace additions facilitated the formation of more finely distributed grains, contributing to grain refinement and preventing recrystallization in the  over-aged state. The enhanced homogeneity of the grains due to trace additions was further supported by fractography studies.